Dualisme Makna Akta Pengakuan Hutang - Roulinta Yesvery Sinaga (Pattimura Legal Journal)
Introduction: Deed of debt recognition as an authentic deed can be made in two forms, namely as a debt agreement or equivalent to a credit agreement and as an assessor agreement of a credit agreement deed that is grosse deed. Both types of debt acknowledgment deeds are still used in public life, the benefits and functions of each deed are different, because the position is different, the impact of the deed is also different.